Передаточные функции электрических колебательных систем - Божко, А.Е.; Попов, С.Г. (Видавничий дім "Академперіодика" НАН України, 2007)
The transfer functions of electrical oscillating systems are defined. The structures of these systems with negative feedbacks are shown.